ENGINEER WP2 SS1 LaserScanner Faro Focus S70 - Previtali, Mattia; Barazzetti, Luigi; Oreni, Daniela; Cuca, Branka; Hadjipetrou, Stylianos; Agapiou, Athos (My University, 2024)
This dataset was created during ENGINEER project activities and is accessible only upon user request and approval by the responsible national authority of Cyprus, namely the Department of Antiquities. The dataset pertains to data acquired at the tombs of the kings using a Faro Focus S70 laser scanner.